2009
DOI: 10.1111/j.1939-165x.2009.00134.x
|View full text |Cite
|
Sign up to set email alerts
|

Breed‐associated variability in serum biochemical analytes in four large‐breed dogs

Abstract: Although many statistically significant breed-related differences in serum biochemical values were observed, the differences were small and unlikely to have clinical relevance or impact medical decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Lastly, the effect Data are presented as mean ± 95% Confidence Interval of dog breed on our values has not been factored. It has been reported that reference values for some biochemical parameters differ between dog breeds (Sharkey et al 2009;Mori et al 2010;Nielsen et al 2010). As such, it is important to consider breed during analysis.…”
Section: Discussionmentioning
confidence: 97%
“…Lastly, the effect Data are presented as mean ± 95% Confidence Interval of dog breed on our values has not been factored. It has been reported that reference values for some biochemical parameters differ between dog breeds (Sharkey et al 2009;Mori et al 2010;Nielsen et al 2010). As such, it is important to consider breed during analysis.…”
Section: Discussionmentioning
confidence: 97%
“…Selection of a suitable and adequate reference sample group, representative of the canine species, is crucial. In addition, breed‐specific RIs for certain particular breeds might be useful for avoiding erroneous clinical decisions, as has been reported for Greyhounds, Lurchers, Bernese Mountain Dogs, and other large breeds in clinical pathology …”
Section: Introductionmentioning
confidence: 99%
“…Reference intervals are used in veterinary medicine to help classify laboratory results reflecting either healthy or diseased animals. Although breed‐specific reference intervals have received little attention in the literature, it is recognised that some breeds have biochemistry variables that differ sufficiently to justify breed‐specific reference intervals (Vondruska and Greco 1974, Sharkey and others 2009). Biochemistry results for greyhounds have been previously evaluated and reference intervals determined with relatively small sample sizes: Steiss and others (2000) n=50; Porter and Canaday (1971) divided sample numbers into males n=22 to 24 and females n=21 to 25; Feeman and others (2003) n=30.…”
Section: Introductionmentioning
confidence: 99%